Cytotoxic Effect of Dentin Desensitizers on Bovine Pulp Derived Cell Viability - Hayriye Esra Ülker; Esma Nur Bülbül; Mustafa Ülker; Türkay Kölüş (Selçuk University, 2023)
Aim: Present study evaluated the cytotoxicity of dentin desentisizing agents on bovine pulp-derived cells (bDPCs). Materials and Methods: Transfected bDPCs cells were exposed to original, ½ and ¼ dilutions of Shield Force Plus, Gluma and Teethmate Desensitizer for 24 h. Culture medium was used as a control group. The bDPCs viability was tested by MTT after 24 hours of exposure. Data were analyzed using the one-way analysis of variance (ANOVA) and the Tukey HSD tests. Results: Neither of the Shield Force Plus and Teethmate Desensitizers change the survival rate of bovine pulp-derived cells when compared to the control (p>0.05). Gluma Desensitizer have cytotoxic effects on bovine pulp-derived cells at all dilutions (p